Surgical morbidity of total laparoscopic hysterectomy for benign disease: Predictors of major postoperative complications. (August 2021) - Casarin, J.; Cromi, A.; Bogani, G.; Multinu, F.; Uccella, S.; Ghezzi, F.
Highlights: Postoperative complication rate following TLH is about 7%. Huge effort should be made to reduce intraoperative complications and conversion. Endometriosis increases the risk of major postoperative events. Abstract: Objective: To estimate rate of perioperative complications and to define risk factors of 30-day major (Clavien-Dindo ≥ 2) postoperative complications of total laparoscopic hysterectomy (TLH) for benign disease. Study design: An uncontrolled single-center single-arm retrospective study. Data of consecutive patients who have undergone TLH for pathologically confirmed benign disease between January 2000 and December 2019 have been analyzed. Perioperative surgical outcomes, occurrence of postoperative complications, readmissions, and reoperations within 30 days from surgery were registered. Univariate and multivariable analyses were performed to determine the factors associated with major (Clavien-Dindo ≥ 2) postoperative complications. Results: Over the study period 3090 patients were included in the study. Conversion to open surgery occurred in 54 (1.7%) cases. Mean operative time for TLH was 87.7 (±1.7) minutes while mean estimated blood loss was 119.5 (+7.4) mL. Overall, postoperative complications were registered in 430 (13.9%) patients, and major events were observed in 208 (6.7%) of the cases. Same-hospital readmissions and reoperations within 30-day from surgery occurred in 78 (2.5%) and 28 (0.9%) patients, respectively. At multivariable analysis, endometriosis (odds ratio: 3.51, 95%CI:1.54–8.30, p = 0.02), the need for conversion to open surgery (odds ratio: 1.26, 98%CI:1.03–12.64, p < 0.001), and the occurrence of any intraoperative complication (odds ratio: 3.10, 95%CI: 1.45–21.61, p < 0.001) were found as independent risk factors for major postoperative complications. Conclusions: Total hysterectomy performed via laparoscopy is associated with acceptable major postoperative complications rate. A huge effort should be made to minimize the occurrence of intraoperative complications and the need for conversion to open surgery. Patients undergoing TLH for endometriosis should be counselled about the increased risk of major postoperative events.